(untitled) (Fiep Bulletin - online, 2014)
Ergonomics is an essential issue for the improvement of working conditions and must be taken seriously by workers, as well as companies and general society. For building construction, it is of particular concern given the fact this is an industry where there are many events of accidents and the existence of many risks. The objective of the present study is to verify the ergonomic conditions of a workstation in a construction warehouse and in order to do so a field research with observation of the activities and of the stockman, the verification using the NIOSH methodology, such as the application of a survey about the adequacy in the relevant Regulatory Standards. The results obtained showed that the layout and disposition of the materials in the warehouse were in accordance to the Regulatory Standards 17 and 18, however the worker haven’t received the adequate training. The results also indicate that the load transported by the worker was above the recommended limits, demanding corrective actions.